-3/7x-1/7

Simple and best practice solution for -3/7x-1/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3/7x-1/7 equation:


x in (-oo:+oo)

(-3/7)*x-(1/7) = 0

(-3/7)*x-1/7 = 0

-3/7*x-1/7 = 0 // + 1/7

-3/7*x = 1/7 // : -3/7

x = 1/7/(-3/7)

x = -1/3

x = -1/3

See similar equations:

| 2x+4y=422 | | Lne^4x=12 | | tan(3x+5)=4 | | x^2+12x+20=9 | | 2x^2-5=-18 | | x^2-12x-20=9 | | 7m-5-3m= | | a+2x=3-ax | | X^3-625x+300=0 | | 2/3×-3=19 | | ln(x+11)-ln(2x)=3 | | 23=x/500/17 | | 23=x/500/15 | | 5/2x=7/2x-5 | | 23=x/500/10 | | 6x^2-4=128 | | 3(b-2)=24 | | 2(b+2)=40 | | Y=500(20)x | | 1/2(6-3x)=25/6 | | 2(b+4)=16 | | R(4r-5)=0 | | 6=(2x)/(0.25-x) | | x+3x+5=33 | | 0.5x=6.25 | | .48x=47 | | 7x=8-2(2x-3) | | -7+49x^2=29 | | 2a+3(a+1)=8 | | 38-7*2+7*3= | | 15x^4-24x^2=0 | | 6(2a-a+1)=24 |

Equations solver categories